Notes on the biology of some commercially important fish species from San Pedro Bay - Mendoza, Crisanne A. (2011)
The growth, gonadal development and diet composition of N. virgatus, U. vittatus, and P. tayenus from San Pedro Bay were determined. A total of 90 N. virgatus, 90 U. vittatus, and 90 P. tayenus were measured and dissected. Results showed that all these species exhibit an isometric growth. The N. virhatus collected were 63.33% immature, unlike that of the U. vittatus and P. tayenus that were mostly gravid and in the ripening stage, respectively. And since, the three species are known to have carnivorous nature, the main food components found in their stomachs were mostly composed of crustaceans, and a few teleosts.